2017
DOI: 10.4218/etrij.2017-0094
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Image Reconstruction for Magnetic Particle Imaging

Abstract: We investigate neural network image reconstruction for magnetic particle imaging. The network performance strongly depends on the convolution effects of the spectrum input data. The larger convolution effect appearing at a relatively smaller nanoparticle size obstructs the network training. The trained single-layer network reveals the weighting matrix consisting of a basis vector in the form of Chebyshev polynomials of the second kind. The weighting matrix corresponds to an inverse system matrix, where an inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…TheDEQ-MPI (Güngör et al 2023) demonstrates improved reconstruction quality and comparable reconstruction speed to ADMM L1 by using a novel deep equilibrium reconstruction with learned consistency. Additionally, while direct image reconstruction approaches based on deep learning have demonstrated superiority in reconstructing simulated data (Chae 2017, von Gladiss et al 2022, they encounter limitations when it comes to real phantom data. Besides supervised learning algorithms, contrastive learning has also been used in MPI reconstruction (Schrank and Schulz 2023).…”
Section: Deep Learning-based Methodsmentioning
confidence: 99%
“…TheDEQ-MPI (Güngör et al 2023) demonstrates improved reconstruction quality and comparable reconstruction speed to ADMM L1 by using a novel deep equilibrium reconstruction with learned consistency. Additionally, while direct image reconstruction approaches based on deep learning have demonstrated superiority in reconstructing simulated data (Chae 2017, von Gladiss et al 2022, they encounter limitations when it comes to real phantom data. Besides supervised learning algorithms, contrastive learning has also been used in MPI reconstruction (Schrank and Schulz 2023).…”
Section: Deep Learning-based Methodsmentioning
confidence: 99%
“…In 2017, Chae [ 67 ] proposed the reconstruction of MPI images using a single-layer fully connected network (Fig. 6 A).…”
Section: Ai Methods For Mpi Reconstructionmentioning
confidence: 99%
“…The development of deep learning technology based on AI has inspired new approaches to MPI reconstruction. Currently, AI is primarily applied in MPI reconstruction [67,68], SM recovery [69], and image postprocessing [70].…”
Section: Ai Methods For Mpi Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chae investigated the MPI reconstruction based on a neural network, and confirmed that a multi-layer with one hidden layer could improve the reconstruction performance [ 64 ]. DIP networks have been recently introduced in deep learning for applications in image processing [ 65 ].…”
Section: Current Sm-based Mpi Reconstruction Methodsmentioning
confidence: 99%